1972
DOI: 10.1021/jo00985a033
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism of acid derivatives

Abstract: NotesH2 (1170 ml) had ceased. The catalyst was removed by filtration (Filter-Cel) and washed with fresh ethanol. The combined filtrates were cautiously neutralized with saturated NaHCOs and concentrated at reduced pressure to ca. 200 ml. This residue was diluted with benzene, washed with H20, and dried (Na2S04). Solvent removal gave a light yellow solid which was filtered through silica gel with 7:3 benzene-ether to give 15.4 g of light tan solid. Crystallization from CH2Cl2-ether gave 11.72 g (71.3%) of dione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

1972
1972
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…The literature claim for formation of H 2 CC(OH)OCOMe as an intermediate has little evidence . It was also claimed that distillation of 2-phenylbutyric anhydride gave a mixture of the anhydride and a mono- and a dienol, but we have shown experimentally that the product is not the enol but a mixture of ethyl phenyl ketene and α-phenylbutyric acid, and that the enol is computationally >13 kcal/mol less stable than the anhydride but calculation suggested that the enol is highly unstable compared with the anhydride …”
Section: Introductioncontrasting
confidence: 57%
“…The literature claim for formation of H 2 CC(OH)OCOMe as an intermediate has little evidence . It was also claimed that distillation of 2-phenylbutyric anhydride gave a mixture of the anhydride and a mono- and a dienol, but we have shown experimentally that the product is not the enol but a mixture of ethyl phenyl ketene and α-phenylbutyric acid, and that the enol is computationally >13 kcal/mol less stable than the anhydride but calculation suggested that the enol is highly unstable compared with the anhydride …”
Section: Introductioncontrasting
confidence: 57%
“…Solvent effects will not change this value much, and, in H 2 O, when the anhydride can take a more stable conformation with a single H 2 O molecule bridging the two CO groups, the pK Enol value will be higher. We conclude, on both experimental and theoretical grounds, that neither 5 nor 6 is formed in observable concentrations in solution, and that the report of their observation [9] is erroneous. a ) DH and DG are relative energies (in kcal/mol) with respect to the most stable anhydride form.…”
mentioning
confidence: 65%
“…No specific assignment could be made for this peak [9]. A broad disappearing peak at 3000 cm À1 was ascribed to an intermolecular Hbond between 4 and 6.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Keto-enol tautomerism (1114), tautomerism of nitrogen containing cyclic and acyclic compounds (1115), and geometrical isomerism of /3-diketonate complexes (1116) have been the subjects of extensive reviews. Studies have been made of the tautomerism of 2-phenylbutyric acid anhydride (1117), rotational barriers in highly substituted diphenyl ethers (1118), and the barrier to pyramidal inversion of diisopropyl-p-tolylstibine (1119), as have studies of conformations of ortho-substituted diphenyl ethers and thioethers (1120), 2-acetylfurans (1121), ,ßunsaturated cyclohexenone derivatives (1122), 2-formylthiophenes and furans (1123), ring inversion 2-halomethyl-l,3-dioxanes (1124), and 1,4-dioxane (1125), and configurations of enamines (1126)(1127)(1128). Rotational isomerism of trifluoroacetones (1129), l,l-bis(dimethylamino)ethylenes (1130), hindered rotation in carbamates (1131) , aryl isopropyl ketones and aryl benzyl ketones (1132) , protonated a-haloacetophenones (1133), and protonated benzaldehydes (1134), conformational studies of cyclic amine oxides (1135), piperidines (1136), alkyl and aryl carbonates (1137), diphenyl ethers (1138), monothiocarbonates (1139), succinic and methylsuccinic acids (1140), 1,3-dioxanes, (1141, 1142), cyclohexaneformaldehyde (1143), tautomerism of 2-amino-2-oxazolin-4-ones (1144), alkyl substituted /3-diketones (1145,1146), and aliphatic acyldiacetylmethanes (1147) have been reported.…”
Section: Conformational Analysis Tautomerism and Rotational Isomersmentioning
confidence: 99%